A case study on adoptive management innovation in China. Issue 1 (4th February 2014) - Lin, Haifen; Su, Jingqin
Abstract : Purpose: – This paper aims to address how management practices successfully implemented somewhere else, namely adoptive management innovation, have been introduced into Chinese firms and then effectively implemented, or to investigate key activities of the generative mechanism through which an adoptive management innovation occurs. Design/methodology/approach: – Since the purpose of management innovation is to utilize organizational resources more efficiently and further their goals, with little intention to pursue differentiation and without any protection from patent, adoptive management innovation has been prevailing around China and even the whole world. Based on the conception of what makes adoptive management innovation unique, this paper attempts to investigate the case of the Organizational Efficiency Management of Jiangxi Mobile in China to identify key activities of adoptive management innovation and develop a two-interlinked-subprocess framework of adoption decision and implementation, aiming to offer suggestions for firms in adopting new management practices. Findings: – The results indicate that adoption of existing management practices or methods from somewhere else is a more complex and logical process rather than a simple one of knowledge transferring. It needs to integrate existing practices into new organizational context and establish their innovative value during implementation. One core element of the process framework is the emphasis on activities of problem diagnoses and realization of the fitness between management practices adopted and the new organizational context, and another one is the sequence of activities in the whole process. Research limitations/implications: – This research is constrained by at least three limitations. First, the authors' findings for the two-subprocess framework of adoptive management innovation need to be further confirmed for more organizations. Second, little attention has been paid to relative advantages of different sequence of activities. Third, when focusing on adoptive management innovation from a process perspective, this research does not address problems such as why some managers pursue innovative opportunities by introducing new practices, how contextual elements, internal elements, and top management teams affect management innovation, or how the performance of adoptive management innovation could be improved in China. Originality/value: – The findings offer some valuable insights for further research in how to explore the generative mechanism of organizational changes or innovations in China and hold important implications for management practices.